A Study on the Importance of Linear Programming in Mathematics: Exploring the Implications and Applications of Linear Programming in Various Disciplines (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Linear programming is one of the central issues of streamlining. Since Dantzig presented the simplex method for settling linear programs, linear programming has been connected in a different go of fields incorporating money matters, operations examine, and combinatorial improvement. From a hypothetical stance, the investigation of linear programming has propelled major developments in the investigation of polytopes, raised geometry, combinatorics, and unpredictability hypothesis.